20 Years of ACE Data: How Superposed Epoch Analyses Reveal Generic Features in Interplanetary CME Profiles. Issue 11 (26th October 2020) - Regnault, F.; Janvier, M.; Démoulin, P.; Auchère, F.; Strugarek, A.; Dasso, S.; Noûs, C.
Abstract: Interplanetary coronal mass ejections (ICMEs) are magnetic structures propagating from the Sun's corona to the interplanetary medium. With over 20 years of observations at the L1 libration point, ACE offers hundreds of ICMEs detected at different times during several solar cycles and with different features such as the propagation speed. We investigate a revisited catalog of more than 400 ICMEs using the superposed epoch method on the mean, median, and the most probable values of the distribution of magnetic and plasma parameters. We also investigate the effects of the speed of ICMEs relative to the solar wind, the solar cycle, and the existence of a magnetic cloud on the generic ICME profile. We find that fast‐propagating ICMEs (relatively to the solar wind in front) still show signs of compression at 1 au, as seen by the compressed sheath and the asymmetric profile of the magnetic field. While the solar cycle evolution does not impact the generic features of ICMEs, there are more extreme events during the active part of the cycle, widening the distributions of all parameters. Finally, we find that ICMEs with or without a detected magnetic cloud show similar profiles, which confirms the hypothesis that ICMEs with no detected magnetic clouds are crossed further away from the flux rope core. Such a study provides a generic understanding of processes that shape the overall features of ICMEs in the solar wind and can be extended with future missions at different locations in the solar system. Plain Language Summary: Interplanetary coronal mass ejections (ICMEs) are magnetized clouds of solar material expelled from the Sun's atmosphere into the interplanetary medium. In the present article, we use plasma and magnetic data from the NASA ACE mission positioned at the Lagrange 1 point and perform statistical studies over the 400 ICMEs detected over the last 20 years. Such an approach, called a superposed epoch analysis, provides a temporal description of the generic features of ICMEs. In particular, we find that ICMEs that propagate faster than their surrounding solar wind still show compressed regions of plasmas and stronger magnetic field. While we find that the 11‐year solar cycle does not affect the generic properties of ICMEs, we observe more extreme events during the active phase. Finally, we also find that a subset of ICMEs, called magnetic clouds and often associated with a stronger and more coherent magnetic field, have the same properties as other ICMEs. This confirms that most ICMEs may be magnetic clouds but which detection is limited by the spacecraft crossing. Such a study, based on long‐term heliospheric missions, allows us to probe physical processes that occur during the propagation of ICMEs, which can help better predict space weather and its consequences. Key Points: ICMEs relatively faster than the solar wind at 1 au show signs of compression throughout their substructures ICME profiles with and without a detected magnetic cloud are similar, showing that all may have MCs but crossed at different locations There is a wider range of population of ICMEs emitted during the active phase of the solar cycle while the typical profiles are the same